Pengembangan Blanded Learning dengan Model Rotasi pada Mahasiswa Calon Guru - Sukma Perdana Prasetya; Nuansa Bayu Segara; Kusnul Khotimah (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2019)
The purpose of this research is to develop blended learning with appropriate rotation model and to test its effectiveness in Cosmography course. This research uses Research and Development method based on the steps of Borg and Gall (1989). The R & D step is done by modifying it to simplify it into three main stages: introduction, development, and testing. Data analysis consisted of three stages: validity test and reliability of research instrument, preliminary test of data in the form of data normality test with kosmogorov-smirnov and homogeneity test with lavene test, hypothesis test using independent t test sample test. This study produces learning tools (RPS, teaching materials, media, jobsheet, assessment sheets) that are eligible to use. The results of this study indicate that there is a significant difference in Cosmographic learning outcomes between groups of students studying using blended learning based on conventional and rotational models. Implementation of the rotation model in learning can increase activity, interest and improve learning outcomes because cosmographic material can be delivered more varied.